Antithrombotic and hemostatic stewardship: evaluation of clinical outcomes and adverse events of recombinant factor VIIa (Novoseven®) utilization at a large academic medical center. (May 2020) - Marsh, Kassandra; Green, David; Raco, Veronica; Papadopoulos, John; Ahuja, Tania
Background: Recombinant factor VIIa (rFVIIa) (Novoseven®) is utilized for the reversal of anticoagulation-associated bleeding and refractory bleeding in cardiac surgery. In August 2015, rFVIIa was transferred from the blood bank to the pharmacy at New York University (NYU) Langone Health. Concordantly, an off-label dosing guideline was developed. The objective of this study was to describe utilization and cost of rFVIIa and assess compliance to our dosing guideline. Methods: We performed a retrospective, observational review of rFVIIa administrations post-implementation of an off-label dosing guideline. All patients who received rFVIIa between September 2015 and June 2017 were evaluated. For each rFVIIa administration, anticoagulation and laboratory values, indications for use, dosing, ordering and administration times, concomitant blood products, and adverse events were collected. Adverse events included venous thromboembolism, stroke, myocardial infarction, and death due to systemic embolism and mortality. The primary endpoint was the utilization of rFVIIa in accordance with the off-label dosing guideline. Secondary endpoints included hemostatic efficacy of rFVIIa, adverse events, blood products administered, and cost-effectiveness of rFVIIa transition to pharmacy. Results: A total of 63 patients [pediatric ( n  = 6), adult ( n  = 57)] received rFVIIa, with the majority of use for refractory bleeding after cardiac surgery. The utilization of rVIIa decreased after development of the off-label dosing guideline and transition from blood bank to pharmacy. The total incidence of thromboembolic events within 30 days was 19.6%; 17.6% arterial and 2% venous; 70% of patients with an adverse event were over 70 years of age. Use of rFVIIa reduced the median number of units of blood products administered. Conclusion: Administration of rFVIIa for cardiac surgery appears to be effective for hemostasis. Transitioning rFVIIa from the blood bank to pharmacy and implementation of a dosing guideline appears to have reduced utilization. Patients receiving rFVIIa should be monitored for thromboembolic events. Elderly patients may be at higher risk for thromboembolic events.